Assessing the source and delivery of organic carbon at a catchment scale using a combined sediment fingerprinting and carbon loss modelling approach - Wiltshire, Catherine; Waine, Toby W.; Grabowski, Robert C.; Glendell, Miriam; Thornton, Barry; Addy, Steve; Meersmans, Jeroen (EGU: European Geophysical Union, 2022)
Quantifying land use sources and understanding the dynamics of organic carbon (OC) in river catchments is essential to reduce both on-site and off-site impacts of soil OC erosion. The lake area of Loch Davan, located in Aberdeenshire, Scotland, has been significantly reduced over the last century due to sediment inputs and, in this study, we aimed to identify the primary source(s) and delivery of OC to the loch’s main feeder stream, Logie Burn and its major tributaries.
Abstract only